Pathophysiology of Circulating Biomarkers and Relationship With Vascular Aging: A Review of the Literature From VascAgeNet Group on Circulating Biomarkers, European Cooperation in Science and Technology Action 18216 - Gopcevic, Kristina R.; Gkaliagkousi, Eugenia; Nemcsik, János; Acet, Ömür; Bernal-Lopez, M. Rosa; Bruno, Rosa M.; Climie, Rachel E.; Fountoulakis, Nikolaos; Fraenkel, Emil; Lazaridis, Antonios; Navickas, Petras; Rochfort, Keith D.; et al. (Frontiers in Physiology, 2021)
The impairment of the arteries due to the exposure to various deleterious factors progresses with time, leading to the phenomenon of vascular aging. Oxidative stress, inflammation, the accumulation of harmful agents in high cardiovascular risk conditions, the changes of the extracellular matrix or the alterations of the epigenetic modification of molecules, are all vital pathophysiological processes leading to changes at the levels of associated circulating molecules. Many of these molecules are found to be markers of vascular impairment and accelerated vascular aging. However, for a molecule to be used as a biomarker of vascular aging, some further requirements must be fulfilled. In this paper, we followed a scoping literature review identifying thirty most important and eight less important biomarkers. Herein, we overview the most important molecules connected with the above-mentioned pathological conditions and study their usefulness as circulating biomarkers of vascular aging.